Abscission cues generated within the abscising organ and perceived by the abscission zone in woody fruit crops - Minglei Zhao; Chun-Lin Shi; Jianguo Li (Fruit Research, 2024)
From an evolutionary perspective, fruit abscission is an intelligent regulatory mechanism by which fruit trees adapt to their environment and ensure offspring. However, from an agricultural production standpoint, unwanted fruit abscission can cause significant loss in fruit yield and economic value. Therefore, investigating the mechanisms of fruit abscission has always been an important focus in the field of plant research. Acquiring a thorough comprehension of the underlying mechanisms responsible for fruit abscission is highly valuable for enhancing fruit crop breeding and optimizing harvesting practices. In this review, we focus on fruit abscission, particularly discussing the nature of abscission cues within the abscising fruit, how these signals are generated and transmitted, and how the abscission zone cells perceive and respond to these signals in woody fruit crops.